2019
DOI: 10.1590/s2175-97902019000217249
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of actinomycetes and characterization of actinomycin-producing strain KRG-1 isolated from Karoo, South Africa

Abstract: In the present study we reported the antimicrobial activity of actinomycetes isolated from aridic soil sample collected in Karoo, South Africa. Eighty-six actinomycete strains were isolated and purified, out of them thirty-four morphologically different strains were tested for antimicrobial activity. Among 35 isolates, 10 (28.57%) showed both antibacterial and antifungal activity. The ethyl acetate extract of strain KRG-1 showed the strongest antimicrobial activity and therefore was selected for further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…In this study, we obtained only seven genera of actinomycetes against tested bacteria and particularly against gram -positive bacteria. Our results support previous studies which showed that the most of isolates of actinomycetes had activity against gram-positive bacteria (Charousova et al 2019;Baskaran et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we obtained only seven genera of actinomycetes against tested bacteria and particularly against gram -positive bacteria. Our results support previous studies which showed that the most of isolates of actinomycetes had activity against gram-positive bacteria (Charousova et al 2019;Baskaran et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Al-H10-1 were extracted by using ethyl acetate (1:1 v/v) from filtrate broth. Charousová I et. al., 2019 also extracted the antimicrobial compounds produced by selected actinomycetes isolated using aridic soil sample collected from Karoo, South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The results were in agreement with Abussaud et al [ 40 ] that found only 5 of 8 active isolates having activity on agar medium produced antagonistic effects in broth culture. These results may be attributed to differences in the culture media composition, inoculum size, or growth conditions that influence the ability of Streptomyces isolates to secrete different active substances on solid growth surfaces and liquid media [ 8 , 42 ]. Another possible explanation is that some active metabolites discharged by streptomycetes may be destroyed or chemically altered during the solvent extraction process [ 8 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results may be attributed to differences in the culture media composition, inoculum size, or growth conditions that influence the ability of Streptomyces isolates to secrete different active substances on solid growth surfaces and liquid media [ 8 , 42 ]. Another possible explanation is that some active metabolites discharged by streptomycetes may be destroyed or chemically altered during the solvent extraction process [ 8 , 42 ]. The extraction of the culture filtrate derived from Streptomyces strains using ethyl acetate was utilized broadly to regain powerful secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%